1991
DOI: 10.1002/abio.370110306
|View full text |Cite
|
Sign up to set email alerts
|

Phytic acid content reduction in canola meal by various microorganisms in a solid state fermentation process

Abstract: Solid state fermentation of canola meal has been carried o u t for the reduction of its phytie acid content using the following microorganisms : Rhiwpus oligosporus NRRL 2990, Aspergillus niger XRC 5765 and NRC 401 121, Aspergillus f i c u u m NRRL 3135 and a wild Saccharomyces cerevisiae strain. The results showed. that all these microorganisms can be used for the reduction of the phytic acid content in the tested material. A . ficuum which completely hydrolyzed the phytic acid in 45 hours was the most effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The increase in DE content may be due to increased starch and fat availability. Previous research35, 36 demonstrated that calcium–phytate complexes bind directly to starches, inhibit α‐amylase activity and subsequently lower starch solubility and digestibility. Fat digestibility was increased by 5% with the inclusion of 1000 FYT kg −1 P lycii phytase compared with a low‐P diet 37.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in DE content may be due to increased starch and fat availability. Previous research35, 36 demonstrated that calcium–phytate complexes bind directly to starches, inhibit α‐amylase activity and subsequently lower starch solubility and digestibility. Fat digestibility was increased by 5% with the inclusion of 1000 FYT kg −1 P lycii phytase compared with a low‐P diet 37.…”
Section: Discussionmentioning
confidence: 99%
“…However, these non-optimized trials were meant to quickly down-select the best microbe for each type of canola meal. Other investigators have previously used a similar submerged incubation process to quickly assess phytase activity of various strains of bacteria, yeasts and fungi when grown on canola and oilseed meals (Nair & Duvnjak, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…One cause of the low availability of minerals in vegetable sources of protein is the presence of phytate and other complexing agents (Nair & Duvnjak, 1991). Phytic acid is found in the cotyledons of legumes or oilseeds; it forms insoluble complexes with minerals which are less available for digestion and absorption in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of toxic or indigestible components such as phytic acid (inositol hexaphosphoric acid), some ethanol-soluble carbohydrates, glucosinolates and polyphenols prevents use of this presscake for human food. One cause of the low availability of minerals in vegetable sources of protein is the presence of phytate and other complexing agents (Nair & Duvnjak, 1991). Phytic acid is found in the cotyledons of legumes or oilseeds; it forms insoluble complexes with minerals which are less available for digestion and absorption in the small intestine.…”
Section: Introductionmentioning
confidence: 99%